Quantum Hall effects : - Ezawa, Zyun F. (World Scientific, 2013)
The Quantum Hall Effect (QHE) is one of the most fascinating and beautiful phenomena in all branches of physics. This title describes the phenomena associated with the interlayer phase coherence in the bilayer system. It formulates the microscopic theory of the QHE based on the noncommutative geometry